The Effectiveness of Project-Based Learning Assisted by Mind Mapping on University Students' Poetry Writing Skills - Efrianto; Ridha Hasnul Ulya; Afnita (Journal of Education Language and Innovation, 2026)
Poetry writing often presents significant challenges for university students, primarily due to difficulties in conceptualizing abstract ideas and organizing them into coherent literary structures. This study aims to analyze the effect of the Project Based Learning (PjBL) model assisted by mind mapping media on the poetry writing skills of undergraduate students majoring in Indonesian Language and Literature Education. A quantitative approach with a one group pretest-posttest design was employed, involving 47 students selected through purposive sampling. Data were collected through a poetry-writing performance test that had been tested for content validity (Aiken's V) and inter-rater reliability, then analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, the Wilcoxon signed-rank test, N-Gain Score, and Cohen's d effect size. The results showed that the mean pretest score of 79.26 increased to 85.85 in the posttest, with the hypothesis test indicating a significance value of p < 0.001, confirming that the PjBL model assisted by mind mapping significantly improved students' poetry writing skills. The average N-Gain Score of 0.285 fell into the medium category, with a large effect size of 0.906. Direct quotations from students' poems further corroborated the quantitative evidence of improvement in diction, imagery, and structural aspects. This study contributes theoretically and practically to the development of creative writing instruction in higher education.